Analytical advances in homeowner flood risk quantification considering insurance, building replacement value, and freeboard - Rahim, Md Adilur; Mostafiz, Rubayet Bin; Friedland, Carol J.; Rohli, Robert V.; Bushra, Nazla (Frontiers in Environmental Science, 2023)
Accurate economic loss assessment for natural hazards is vital for planning, mitigation, and actuarial purposes. The widespread and costly nature of flood hazards, with the economically disadvantaged disproportionately victimized, makes flood risk assessment particularly important.Here, flood risk is assessed as incurred by the homeowner vs. by the flood insurer for insured U.S. properties through the derivation of average annual loss (AAL). AAL is estimated and partitioned using Monte Carlo simulation at the individual home scale considering insurance coverage and deductible, and home freeboardfirst-floor height (i.e., elevation height of the first floor above the base flood elevationground), to determine the homeowners' AAL proportion (i.e., apportionment factor) for building and contents, distinguished from that borne by the insurer. In general, AAL estimates suggest that a large portion of the U.S. property flood risk is borne by flood insurer. The flood insurance policy deductible directly influences the apportionment factor whereby higher deductibles leave homeowners with higher annual risk; however, the apportionment factor remains relatively insensitive to coverage values, especially for higher coverage amounts. The homeowner's flood risk is further reduced by freeboard, with AAL following an exponential decay trend as freeboard increases, but the apportionment factor appears relatively insensitive to freeboard. These results reveal new perspectives about how flood insurance protects homeowners from flood risk. In general, results inform the proactive decision-making process that allows homeowners to self-assess their degree of preparation and vulnerability to the devastating economic impacts of flood.